1985
DOI: 10.1103/physreva.31.2534
|View full text |Cite
|
Sign up to set email alerts
|

Relative intensities of 2s22pk-2s2et al.

Abstract: Measured relative intensities of a number of allowed 2s 2p -2s2p +' transitions (60 -200 A) in the F I -to B I -like ions of titanium, chromium, iron, nickel, and germanium are compared with values from level-population calculations. The measurements are from Princeton Large Torus (PLT) tokamak plasmas with electron densities of -2.5)&10' cm . For titanium and chromium, data from plasmas with densities of -5&10' cm are also presented; a number of densitydependent line-intensity ratios are found. The spectra we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…The uncertainties for the Linsky et al and Mathioudakis (1999) observations are those quoted by these authors, and the Dupree et al (1993) uncertainty set equal to the average of the Linsky et al uncertainties. We also include a solar‐flare value from the OSO‐5 spacecraft (Kastner, Neupert & Swartz 1974; Mason et al 1984: uncertainty estimated from the calibration necessary in this measurement) and values from the Princeton Large Torus (PLT) tokamak with electron densities measured by a microwave interferometer (Stratton, Moos & Finkenthal 1984; Stratton et al 1985). With the uncertainties on the Capella and solar points, it would seem that none of the points are much above the low‐density limit, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainties for the Linsky et al and Mathioudakis (1999) observations are those quoted by these authors, and the Dupree et al (1993) uncertainty set equal to the average of the Linsky et al uncertainties. We also include a solar‐flare value from the OSO‐5 spacecraft (Kastner, Neupert & Swartz 1974; Mason et al 1984: uncertainty estimated from the calibration necessary in this measurement) and values from the Princeton Large Torus (PLT) tokamak with electron densities measured by a microwave interferometer (Stratton, Moos & Finkenthal 1984; Stratton et al 1985). With the uncertainties on the Capella and solar points, it would seem that none of the points are much above the low‐density limit, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Foster et al (1994) have determined cross-sections and rate coefficients for the 2s 2 2p 5 2 P 3/2 → 2s 2 2p 5 2 P 1/2 transition in the Ti XIV, Ni XX, Zn XXII, and Mo XXXIV ions by considering the proton, deuteron, trition and α particles impact by using the calculated radiative decay rates in the closed-coupling method. Also, observations of the spectral lines due to both the allowed and forbidden transitions of the Fe XVIII and Ni XX ions are reported (Suckewer & Hinnov 1979;Doyle 1983;Stratton et al 1985;Acton et al 1985;Wang et al 1988). Precise values of the transition probabilities for the highly charged ions that are due to the forbidden channels are of particular interest to physicists for diagnosing the low-density magnetically confined high temperature laboratory plasma generated in tokamak (Currell 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Proton collisions can change populations of closely spaced fine structure levels, such as Ca XVI − Ca XIII ground levels. Stratton et al (1985) demonstrated that for the Ti, Cr, Fe and Ni ions this effect is weak, with the exception of carbon-like ions. Since electron impact excitation is the main source of excited level population at the typical tokamak temperature and density, the accuracy of the electron excitation rate coefficients is critical for calculating accurate spectral line intensities.…”
Section: Details Of Computationsmentioning
confidence: 98%